The Bethesda system for reporting thyroid cytology: a prospective study in a tertiary care institute along with review of literature - Bhatnagar, Avni; Mardi, Kavita; Sood, Shivani; Kaushal, Vijay; Gupta, Kanishk (International Journal of Research in Medical Sciences, 2020)
Background: The Bethesda system for reporting thyroid cytology (TSBRTC) was devised by the National Cancer Institute (NCI) to obtain uniformity, reproducibility and a defined management protocol while dealing with thyroid lesions. This study was undertaken with the aim to see the benefits of adopting TBSRTC in the diagnosis of thyroid FNAC, and identify the malignancy risk of each category. Methods: This cross-sectional study was conducted in Indira Gandhi Medical College, Shimla, Himachal Pradesh from June 2016 to July 2017 on 181 thyroid FNACs which were reported according to the Bethesda system for reporting thyroid cytopathology (TBSRTC) under six categories: (I) non-diagnostic/unsatisfactory (II) benign (III) atypia of undetermined significance/follicular lesion of undetermined significance (IV) follicular neoplasm/suspicious for follicular neoplasm (specify if Hurthle cell (oncocytic) type (V) suspicious for malignancy (VI) malignant. Histopathological diagnosis was available for 65 cases where thyroidectomy was performed. Malignancy risk was calculated for each category. Sensitivity, specificity, positive and negative predictive values for TBSRCT were also calculated. All the data was analyzed in SPSS software version 22.0 (IBM, USA). Results: Benign lesions constituted the major bulk. After the use of TBSRTC, there was increased ability to look for follicular neoplasms, improvement in making definitive diagnosis of the cases, an improvement in diagnostic accuracy, and we were in line with the implied risk outlined by TBSRTC in most of the cases. Conclusions: Application of TBSRTC results in uniformity in reporting among pathologists and better interdisciplinary communication and patient management.